(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
This article examines the development of students’ speech competence in mother tongue classes, focusing on the use of interdisciplinarity as a pedagogical approach. The study addresses the pedagogical challenge of enhancing students’ speech competence in their native language by incorporating interdisciplinary methods and approaches into classroom instruction. The research highlights the importance of integrating various disciplines, such as literature, history, and social science, to foster students’ linguistic skills and enhance their overall communication abilities. By exploring the benefits and challenges associated with interdisciplinarity in mother tongue classes, this article offers insights into effective strategies for improving students’ speech competence and promoting a holistic learning experience. The findings of this research contribute to the ongoing discourse on language education, emphasizing the significance of interdisciplinary approaches in nurturing students’ linguistic competencies within their native language classrooms.